2017
DOI: 10.1177/0957650917692153
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady vortical flow simulation in a Francis turbine with special emphasis on vortex rope behavior and pressure fluctuation alleviation

Abstract: Hydro turbines operating at partial flow conditions usually have vortex ropes in the draft tube that generate large pressure fluctuations. This unsteady flow phenomenon is harmful to the safe operation of hydropower stations. This paper presents numerical simulations of the internal flow in the draft tube of a Francis turbine with particular emphasis on understanding the unsteady characteristics of the vortex rope structure and the underlying mechanisms for the interactions between the air and the vortices. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…According to Hidalgo et al [4], the C p can be equal to −σ when p s achieves values of p v , which is observed in Figure 7 for ξ values among 0.2 and 0.8. However, the experimental study presents differences at (d) 0.9c due to the fact that C p is higher than −σ with more pulses than numerical results, which are related to the cavity collapse process [3]. For that, the k − ω SST SAS approach matched better the trend of the experimental results than ILES approach.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…According to Hidalgo et al [4], the C p can be equal to −σ when p s achieves values of p v , which is observed in Figure 7 for ξ values among 0.2 and 0.8. However, the experimental study presents differences at (d) 0.9c due to the fact that C p is higher than −σ with more pulses than numerical results, which are related to the cavity collapse process [3]. For that, the k − ω SST SAS approach matched better the trend of the experimental results than ILES approach.…”
Section: Resultsmentioning
confidence: 76%
“…Studies of unsteady cavitating flow around hydrofoils are important to understand the cavitation dynamic behavior and its impact in hydraulic machinery [1,2]. Experimental studies have shown limitations such as: equipment uncertainty, costs and experiments calibration [3]. Therefore, CFD is an alternative way to study the aforementioned phenomenon based on numerical models [4].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al 23 and Gu et al 24 carried out experiments of pressure fluctuation measurements to get further insight into dynamic properties of the vortex in different cyclone separators. Luo et al 25 studied the variation of pressure fluctuation caused by vortex rope under different gas injection, and the air occupation at the draft tube center for the stable operation was proposed. However, certain unusual characteristics of pressure fluctuation induced by vortices are still to be solved urgently in the ultra-low specific-speed centrifugal pump with a complex vorticity field.…”
Section: Introductionmentioning
confidence: 99%
“…Cm is a coefficient related to the difference between the smallest and the averaged grid dimension depends on the ratio of grid dimension generated in each case of analysis. Table 1 shows a comparison with different Cm value for predicting hydraulic performance of a Francis turbine, whose geometry and performance are explained in the literature [14]. The data for numerical simulation are marked with "Num", and the tested data are marked with "Exp.".…”
Section: Turbulence Modelmentioning
confidence: 99%
“…Therefore, it is evident that PANS is suitable for predicting complex turbulence behavior of large scale unsteadiness. Though PANS shows excellent improvements to predict cavitating turbulent flows [14,15,16], there is no information regarding the prediction of liquid-solid two phase flow and sediment erosion by applying this method.…”
Section: Introductionmentioning
confidence: 99%